Drug-independent NADPH-consuming micelles collaborate with ROS-generator for cascade ferroptosis amplification by impairing redox homeostasis. (February 2023) - Yu, Fangying; Shang, Xuwei; Wang, Zixu; Zhu, Yun; Chen, Simin; Yuan, Hong; Hu, Fuqiang
Abstract: Ferroptosis as promising antitumor therapy strategy could be comprised by intracellular antioxidants, especially GSH and thioredoxin (Trx). They are both cofactors of Gpx4, the enzyme catalyzing the production of lipid peroxides to relieve oxidative stress, which drives the acquired ferroptosis resistance in tumors. Herein, the NADPH-consuming micelles are specially designed, which could collaborate with the ROS generating photodynamics therapy (PDT) by depleting intracellular GSH and Trx under hypoxia condition, resulting in ruined redox homeostasis and the final cascade amplified ferroptosis. The tailored micelle was briefly prepared by conjugating hypoxia-sensitive segment p-nitrobenzyl chloroformate (PNZ-Cl) to the hydrophilic chitosan (CS), the resulting micelle was further modified with photosensitizer Ce6 via PEG linkage. When receiving laser irradiation, the photosensitizer would generate ROS and consume oxygen in the meanwhile. The resulting anabatic hypoxia in turns promote the NTR-catalyzed electron-accepting response of micelles, with evidently enhanced NADPH consumption and ultimately ruined redox homeostasis, contributing to cascade amplified ferroptosis with robust ROS. Most importantly, the accompanied immunogenic cell death (ICD) and releasing danger-associated molecular patterns (DAMPs) could boost dendritic cells (DCs) maturation and the subsequent T-cell-mediated profound immune response. Collectively, the work excavates the other biochemical reaction during the hypoxia-sensitive process of C–N–Ce6 by diminishing intracellular GSH and Trx, providing a candidate of ferroptosis inducers against solid tumors. Graphical abstract: Image 1